2021
DOI: 10.3389/fpsyg.2021.743361
|View full text |Cite
|
Sign up to set email alerts
|

Communication, Social Networks and Sustainable Development Goals: A Reflection From the Perspective of Social Marketing and Happiness Management in the General Elections in Spain

Abstract: The challenges imposed by the global development agenda imply reflecting on the role and contribution of political parties to development processes in the online environment. Social networks have been characterised as a part of the strategies of political campaigns, as it allows political leaders to establish bidirectional communication with citizens. In this context, the present study aims to empirically explore the leading Spanish political formations' publications from a social marketing perspective. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
1
11
0
2
Order By: Relevance
“…The fact that active and effective communication and the selection of appropriate information tools can be a way of managing sustainable development processes was confirmed by the results of our research, which showed that more than half of the respondents are sometimes influenced and encouraged to act in a sustainable manner by the information they receive about sustainable development and its implementation, and that almost a quarter of the respondents have a strong influence on their behaviour towards sustainable development principles. These findings are supported by research by other authors (Lee, 2016;Galiano-Coronil et al, 2021) showing the important role of communication in the implementation of a consumer-oriented framework that includes sustainability issues, promoting sustainable thinking and sustainable consumption. Nadanyiova et al (2020) also acknowledge that green marketing, as part of socially responsible communication, can positively influence the attitudes of individual target groups towards responsible consumption and can add value to goods, products and services that are related to environmental aspects and social responsibility towards the environment, while Primožič et al (2022) point out the importance of a communication strategy related to climate change, global warming, sustainability etc.…”
Section: Entrepreneurship and Sustainability Issuessupporting
confidence: 77%
See 1 more Smart Citation
“…The fact that active and effective communication and the selection of appropriate information tools can be a way of managing sustainable development processes was confirmed by the results of our research, which showed that more than half of the respondents are sometimes influenced and encouraged to act in a sustainable manner by the information they receive about sustainable development and its implementation, and that almost a quarter of the respondents have a strong influence on their behaviour towards sustainable development principles. These findings are supported by research by other authors (Lee, 2016;Galiano-Coronil et al, 2021) showing the important role of communication in the implementation of a consumer-oriented framework that includes sustainability issues, promoting sustainable thinking and sustainable consumption. Nadanyiova et al (2020) also acknowledge that green marketing, as part of socially responsible communication, can positively influence the attitudes of individual target groups towards responsible consumption and can add value to goods, products and services that are related to environmental aspects and social responsibility towards the environment, while Primožič et al (2022) point out the importance of a communication strategy related to climate change, global warming, sustainability etc.…”
Section: Entrepreneurship and Sustainability Issuessupporting
confidence: 77%
“…It also shows how companies' sustainability marketing communications vary across different social media. Galiano-Coronil et al (2021) argue that social networks have been described as part of political campaign strategies because they allow political leaders to establish a two-way connection with citizens. This study aims to empirically investigate leading Spanish political publications from a social marketing perspective.…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…It may lead to a more social, inclusive, prosperous and egalitarian ecosystem. In this way, it makes the culture of organisations around the pillars of happiness management, social marketing and the Sustainable Development Goals shine (Galván-Coronil et al. , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…De hecho, desde la primera campaña electoral de Obama, en el año 2008, Twitterha sido profusamente estudiado, fundamentalmente desde el punto de vista de la comunicación política y electoral (Mangerotti, Ribeiro y González-Aldea, 2022;Rodríguez Vázquez y Jorquera, 2021;Valenzuela, Correa y Gil de Zuniga, 2018;Bracciale y Martella, 2017;Campos-Domínguez, 2017;Enli, 2017;Guerrero-Solé y Mas-Manchón, 2017;López-Meri, Marcos-García y Casero-Ripollés, 2017;Waisbord y Amado, 2017;Bucheli, 2014;Kreiss, 2016;López-García, 2016;Jürgens y Jungherr, 2015;García y Zugasti, 2014;Dang-Xuan et al, 2013;Criado, Martínez y Silvan, 2013). Y, recientemente, como se ha apuntado en párrafos precedentes, la lamentable emergencia sanitaria generada por la COVID19, viene impulsando también un relevante corpus científico en torno al estudio de esta red social respecto a la desinformación y a la consecuente infodemia que caracterizó los primeros meses de su gestión (Rosenberg, Syed y Rezaie, 2020;Mavragani, 2020;Higgins et al, 2020;Cousins et al, 2020;Hernández-García y Giménez-Júlvez, 2020;Park, Park y Chong, 2020;Solomon et al, 2020;Galiano-Coronil, Jiménez-Marín, y Tobar-Pesantez, 2021).…”
Section: Estado De La Cuestión: El Valor Institucional De Twitterunclassified